Ketone Supplementation: Meeting the Needs of the Brain in an Energy Crisis - Poff, Angela M.; Moss, Sara; Soliven, Maricel; D'Agostino, Dominic P. (Frontiers in Nutrition, 2021)
Diverse neurological disorders are associated with a deficit in brain energy metabolism, often characterized by acute or chronic glucose hypometabolism. Ketones serve as the brain’s only significant alternative fuel and can even become the primary fuel in conditions of limited glucose availability. Thus, dietary supplementation with exogenous ketones represents a promising novel therapeutic strategy to help meet the energetic needs of the brain in an energy crisis. Preliminary evidence suggests ketosis induced by exogenous ketones may attenuate damage or improve cognitive and motor performance in neurological conditions such as seizure disorders, mild cognitive impairment, Alzheimer’s disease, and neurotrauma.